Research on the normalized assistance mechanism for rural low-income population under the digital economy——Taking the rural areas of Guangxi as an example - Mengyu Xiao; Dongsheng Liao (Journal of Frontier in Economic and Management Research, 2025)
The digital economy emerged as the times require in the new round of information technology revolution. It is a new kinetic energy and a new engine to promote high-quality economic development. It also provides a good opportunity for the digital construction of rural agriculture and rural revitalization. Based on the era of digital economy, this paper analyzes the status quo of the normalized assistance mechanism for the rural low-income population in Guangxi, and points out from six aspects: industrial assistance, intelligent assistance, employment assistance, consumption assistance, support of aspirations and intelligence, and multi-subject assistance. At present, the problems existing in the normalized assistance for the rural low-income population in Guangxi, and suggestions for building a normalized assistance mechanism for the rural low-income population are put forward from these six aspects, so as to accelerate the realization of common prosperity for the rural low-income population.